PENGETAHUAN MASYARAKAT TENTANG MAKNA NANASI SEBAGAI SIMBOL PERSATUAN MASYARAKAT BUTON (Studi di Kelurahan Lamangga Kecamatan Murhum Kota Baubau) - Ayu Indah Lestari; La ode Topo Jers; Hasniah Hasniah (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2018)
This study aims to find out and describe the knowledge of the Buton community in Kelurahan Lamangga, Murhum Subdistrict, Bau-Bau City, about the meaning of nanasi as a symbol of community unity and the application of the meaning of nanasi symbols in the lives of local people. This study uses ethnographic methods by collecting data through observation and in-depth interviews. The results of this study show several things, namely: (1) public knowledge about the meaning of nanasi as a symbol of the unity of the Buton community in Lamangga Village, related to the life philosophy of the meaning contained in each part of nanasi which is used as a symbol of unity. This is the basis for the formation of behavioral actions and characteristics possessed by the people of Buton, both individually and in groups. In each part, nanasi has meant starting from the roots, leaves, stems, fruits to the top. The meaning of the symbol relates to philosophical values in the life of Buton society, concerning the value of faith, moral values and also the nature of the independence of the Buton community, as a guideline in the order of moral awareness and patterns of social life that have been inherited from ancestors; (2) the application / application of the meaning of nanasi symbols in the life of Buton people in Lamangga Village began to decline due to lack of understanding and differences in interpretation by individual communities, so that only a small portion of the community still applied the knowledge of the meaning of nanasi symbols, especially among local teenagers.